2016
DOI: 10.1007/s00595-016-1437-y
|View full text |Cite|
|
Sign up to set email alerts
|

Rib resection using a pneumatic high-speed power drill system for lung cancer with chest wall invasion: our clinical experience

Abstract: Rib resection for chest wall tumors, including lung cancer with chest wall invasion, is usually performed through open thoracotomy. Resection of part of the external rib cage requires an elongated or additional incision depending on the location and extension of the tumor, eventually becoming more invasive to patients. We recently introduced a technique of rib resection using a pneumatic high-speed power drill system known as "air tome". This novel technique is easy to perform through a small incision or even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…20 In addition to spine surgery, it has also been applied to other surgeries requiring bone resection. 9,21 The advantages of a surgical air drill are as follows: (i) easy to use; (ii) it enables quick and precise bone cuts without damaging surrounding tissues; and (iii) it results in flat bone surface. Handling of the drill is easy, even for inexperienced urologists, and we found that no difficulties were reported in any of our cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 In addition to spine surgery, it has also been applied to other surgeries requiring bone resection. 9,21 The advantages of a surgical air drill are as follows: (i) easy to use; (ii) it enables quick and precise bone cuts without damaging surrounding tissues; and (iii) it results in flat bone surface. Handling of the drill is easy, even for inexperienced urologists, and we found that no difficulties were reported in any of our cases.…”
Section: Discussionmentioning
confidence: 99%
“…A high‐speed air drill has been considered indispensable for spine surgery 20 . In addition to spine surgery, it has also been applied to other surgeries requiring bone resection 9,21 . The advantages of a surgical air drill are as follows: (i) easy to use; (ii) it enables quick and precise bone cuts without damaging surrounding tissues; and (iii) it results in flat bone surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chest wall is the most frequently neighboring structure involved in locally advanced lung tumors and its resection is required for a radical treatment (8).…”
Section: Discussionmentioning
confidence: 99%